Pemenuhan Aksesibilitas bagi Penyandang Disabilitas di Kawasan Wisata Jam Gadang dan Sekitarnya, Kota Bukittinggi, Sumatera Barat - Putra Rizkiya; M Rafi Mahdy; Zahrul Fuady (Fakultas Teknik, 2023)
Persons with disabilities are vulnerable, and their rights are often ignored. Persons with disabilities have the right to visit tourist sites. Bukittinggi City is a tourist city in West Sumatra Province. Its most popular tourist areas is the Jam Gadang tourist area and its surroundings, which include Jam Gadang, Fort De Kock Fort, and the Kinantan Wildlife and Cultural Park. People with disabilities are rarely seen in the Jam Gadang tourist area and its surroundings, both at tourist attractions and on the pedestrian paths connecting the three tourist attractions. This research aims to determine the fulfillment of accessibility for persons with disabilities in the Jam Gadang tourist area and its surroundings regarding tourist access and pedestrian access. Data was collected through field observations and questionnaires. The analysis was descriptive quantitative using scoring analysis. The result shows that the fulfillment of accessibility in the study area is generally